Freud : a modern reader - Perelberg, Rosine Jozef; Wiley InterScience (Online service) (London ; Philadelphia : Whurr, 2005)
"This long-awaited textbook makes accessible the ideas of one of the most important thinkers of our time, as well as indicating how Freud's theories are put into clinical practice today. The collection of papers has been written by some of the most eminent psychoanalysts, both from Britain and abroad, who have made original contributions to the field. Each chapter introduces one of Freud's key texts, and links it to contemporary thinking in psychoanalysis. The book combines a deep understanding of Freud's work with some of the most modern debates surrounding it."--Jacket.
Includes bibliographical references and index.
Print version record.
Keywords: Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939.; Psychoanalysis; Freudian Theory; Psychoanalysis; PSYCHOLOGY -- Movements -- Psychoanalysis; Psychoanalysis; Electronic books